Developing Quizizz Based Learning Media in Teaching Reading - Yanuarti Apsari; Rissa San Rizqiya; Nissa Kamila Auliya (Journal of English Education and Teaching, 2023)
The objectives of this study are to (1) identify the process of developing the product, (2) find out the feasibility of the product and (3) to find out students’ responses toward the product. The research method used in this research was the Research and Development (R & D) method, with the ADDIE development model. The respondents of this study were first semester students in English department who are taking the subject of reading for general purposes and two experts who assess the validity of the product content and the validity of media. The data collection methods in this study were observation, interview and questionnaires. The results showed that the process of developing the product has completed with the ADDIE model, which consisted of five stages namely Analysis, Design, Development, Implementation, and Evaluation. Second, the product was feasible. It was supported by the validators' result value, which felt into the "Very Good" categories. Third, the product that has been tested in the class received positive responses from the students. Therefore, it can be concluded that the use of quizizz based learning media is recommended to be applied in reading class. This media is beneficial in improving students’ interest in reading.